2008
DOI: 10.1007/s11920-008-0043-0
|View full text |Cite
|
Sign up to set email alerts
|

Youth with substance abuse and comorbid mental health disorders

Abstract: Patients with co-occurring disorders (CODs) have a substance use disorder (SUD) and at least one other mental health diagnosis. Many patients with a non-SUD mental health diagnosis also have an SUD, whereas most patients with SUDs have other co-occurring psychiatric disorders. Recognition is growing regarding the importance of identifying and treating CODs. This article reviews the magnitude of CODs, theories by which CODs develop, treatment options for CODs (including psychotherapeutic and psychopharmacologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 46 publications
1
17
0
Order By: Relevance
“…A review of co-occurring disorders among youths underscored the role of motivation in seeking treatment and the potential of motivational interviewing (9). This strategy demonstrated mixed results in a homeless substance-using youth population (10), but it requires further study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A review of co-occurring disorders among youths underscored the role of motivation in seeking treatment and the potential of motivational interviewing (9). This strategy demonstrated mixed results in a homeless substance-using youth population (10), but it requires further study.…”
Section: Discussionmentioning
confidence: 99%
“…Programs that address youths' basic needs and vocational and life skills have demonstrated important mental health outcomes (10), and case management has been linked to increased mental health service use among homeless youths (12). The fragmented nature of services described by participants is widely noted in literature on homeless youths (8) and youths with co-occurring disorders, underlining the importance of integrated and comprehensive services (9). Ontario has adopted the philosophy that "every door is the right door" (13).…”
Section: Discussionmentioning
confidence: 99%
“…Given the high incidence of co-occurring problems among adolescents entering substance use treatment, and findings regarding the moderating impact of these problems on treatment outcomes, researchers have outlined the case for integrated treatments that address both the SUD and the co-occurring psychiatric problems (Armstrong & Costello, 2002; Bender, Springer, & Kim, 2006; Couwenbergh et al, 2006; Lamps, Sood, & Sood, 2008; Libby & Riggs, 2005; Riggs, Levin, Green, & Vocci, 2008). Specific treatment features recommended for an integrated approach to treating these adolescents include: a) validated intake assessments that adequately identify psychiatric and substance use problems (Bender et al, 2006; Couwenbergh et al, 2006; Riggs, 2003); b) engagement and retention techniques that rely on an empathic and non-confrontational approach (Lamps et al, 2008; Riggs, 2003); c) a fiexible clinical approach that includes input from participants when developing treatment plans (Bender et al, 2006); d) inclusion of family and available community resources (Riggs, 2003); e) developmentally appropriate and gender/culturally competent treatment (Armstrong & Costello, 2002; Bender et al, 2006); f) a multifaceted approach that addresses several domains including problem-solving and decision-making skills, affect regulation, impulse control, communication skills, and peer and family relations (Bender et al, 2006; Couwenbergh et al, 2006; Libby & Riggs, 2005; Riggs, 2003); g) homework assignments (Bender et al, 2006); and (h) paired medication monitoring and adherence procedures with medication (when indicated) (Riggs, 2003; Riggs et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…This highlights the complexity of planning treatment efforts for inhalant users and the need to address a broad range of problems. In addition, it should also be remembered that not only engaging in juvenile delinquency strongly predisposes adolescents to use substances [50], including inhalants, but that chronic inhalant use creates an additional burden in terms of long-lasting sequela, such as increased cognitive impairment, problems with impulse control, and mental health problems [11, 12], which in turn increase the risk for repeated antisocial involvement.…”
Section: Discussionmentioning
confidence: 99%
“…Even experimental use of inhalants has been linked to adolescent risk-taking and disruptive behaviors [9, 10], whereas the chronic use may lead to more serious and long-lasting mental and somatic health problems [11, 12]. Studies of adolescent inhalant users have found that they are more likely than non-users to report poor family relations, disrupted living situations, academic problems [13, 14] and are at increased risk of multiple drug use [13].…”
Section: Introductionmentioning
confidence: 99%